Contesting consent in sex education*. Issue 3 (4th May 2018) - Gilbert, Jen
Abstract: This paper explores discourses of affirmative consent in sex education curriculum and policy. It traces the ways in which discourses of consent have emerged in sex education debates, focusing first on the activism of two young women in Ontario, Canada who lobbied the provincial government to include discussions of consent in a new Health and Physical Education (HPE) curriculum. Their activism is instructive for the ways in which their lobbying was eventually subsumed into the logics of curriculum, with learning outcomes and lesson plans taming the passion of their protest. As others see in sex education the answer to sexual violence, we cannot forget that sex education is, in part, a defence against passion, and that consent – once swallowed up by HPE – might also work to tame the unruliness of sexuality. Turning to age of consent laws – another arena where discourses of consent discipline the sexuality of young people – I ask how our pedagogical and legal address to sexuality paradoxically refuses its force. This is the central argument of this article – namely, that the concept of consent brings with it, into education, a procedural logic that misrecognises sexuality as a transparent, communicative, and rational experience and mistakes compliance for learning.